Gastrodiplomacy Indonesia di Belanda Era Pemerintahan Joko Widodo - Yeremias Yeremias; Erna Kurniawati (Jurnal Paradigma, 2018)
The purpose of this research is to identify kind of Indonesian diplomacy through gastrodiplomacy.